2007
DOI: 10.1038/nsmb1334
|View full text |Cite
|
Sign up to set email alerts
|

A charged and contoured surface on the nucleosome regulates chromatin compaction

Abstract: Local nucleosome-nucleosome interactions in cis drive chromatin folding, whereas interactions in trans lead to fiber-fiber oligomerization. Here we show that peptides derived from the histone H4 tail and Kaposi's sarcoma herpesvirus LANA protein can replace the endogenous H4 tail, resulting in array folding and oligomerization. Neutralization of a LANA binding site on the histone surface enhanced rather than abolished nucleosome-nucleosome interactions. We maintain that the contoured nucleosome surface is cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
120
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(130 citation statements)
references
References 15 publications
8
120
1
1
Order By: Relevance
“…These data suggest that this band represents interaction of the H4 tail domain with the H2A pocket previously observed in crystal structures of nucleosome core particles (27). These results are consistent with previous reports that the H4 tail binds to a pocket on the surface of H2A, generating an on May 9, 2018 by guest http://mcb.asm.org/ internucleosomal interaction to enhance folding of nucleosome arrays (10,13,33,49). Interestingly, although the nucleosome array is expected to exist as a completely extended structure with little or no internucleosome interactions in the absence of MgCl 2 (25,30,31), cross-linking between H4 and H2A was detectable under these conditions (Fig.…”
Section: Vol 29 2009 Interarray Interactions Of the H4 Tail In Chrosupporting
confidence: 82%
See 1 more Smart Citation
“…These data suggest that this band represents interaction of the H4 tail domain with the H2A pocket previously observed in crystal structures of nucleosome core particles (27). These results are consistent with previous reports that the H4 tail binds to a pocket on the surface of H2A, generating an on May 9, 2018 by guest http://mcb.asm.org/ internucleosomal interaction to enhance folding of nucleosome arrays (10,13,33,49). Interestingly, although the nucleosome array is expected to exist as a completely extended structure with little or no internucleosome interactions in the absence of MgCl 2 (25,30,31), cross-linking between H4 and H2A was detectable under these conditions (Fig.…”
Section: Vol 29 2009 Interarray Interactions Of the H4 Tail In Chrosupporting
confidence: 82%
“…They further showed that the initial step in the process involves self-association of monomeric nucleosome arrays (55 S) into oligomeric structures approximately 10 times larger than the arrays (about 500 S), without appreciable accumulation of species of intermediate sizes. As the salt is increased further, these ϳ500-S structures continue to self-associate into extremely large complexes that sediment in excess of Ͼ Ͼ10,000 S. These observations provide a rigorous physicochemical basis for a simple microcentrifuge-based assay now routinely used to study self-association (5,10,25,30,33,43). Association of linker histones also pushes the equilibrium toward the largest species (8,30).…”
mentioning
confidence: 89%
“…This finding supports the idea that access to the H4 tail after DNA damage is restricted through interaction of H4 with the acidic patch on the nucleosome surface. Because the H4 tail and GFP-LANA both bind to this acidic patch (30,31), displacement of the H4 tail, either by LANA peptide or Anp32e (which removes H2A.Z and eliminates the acidic patch) will promote H4Ac after DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we used the LANA protein of Kaposi's sarcoma herpes virus (27). LANA protein binds tightly to the acidic patch (30,31), using the same acidic amino acids to which the H4 tail binds. The 23 amino acid domain of LANA, which binds to the acidic patch, and a control, in which an essential arginine was mutated to glycine (30), were fused to GFP and expressed in cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the reduction in silencing and changes in heterochromatin caused by LRS mutations are probably not a result of SIR dissociation from HML. As the solvent-accessible surface is involved in higher-order chromatin formation (Chodaparambil et al 2007;Zhou et al 2007), it is possible that LRS contributes to silencing by aiding the formation of high-order heterochromatin structure.…”
Section: Resultsmentioning
confidence: 99%